(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
Racism is a phenomenon about which several studies have been developed. This work aimed to verify the occurrence racist bias in the field of Public Security. Fifteen military police officers from the municipality of Feira de Santana participated in the study. The instruments used were a concept questionnaire and the Go-IRAP. The software presented three test blocks and a maximum of four training blocks. It was presented, in the blocks, a model stimulus (the phrase “white people are” or “black people are”), and, below that, targeting stimuli (positive or negative words). The results showed a pro-black bias in the research participants. The small sample of participants made it difficult to analyze the data and gave little robustness to the possible analyzes. Future research is encouraged in this area with larger samples.